Strategi Promosi dalam Meningkatkan Investasi : Studi Kasus Galeri Investasi FEBI UINSU - Ahmad Firdaus Lingga; Nur Ainun Ningsih; Yulita Astri; Muhammad Ikhsan Harahap (Universitas Muhammadiyah Enrekang, 2023)
This research was conducted to find out the right promotional strategy to increase interest in investing, especially students. Researchers use qualitative research types in their research by applying a descriptive approach. Primary data in the study was obtained by interviewing directly an institution concerned. While the secondary data contained in the research is obtained through scientific literature in the form of scientific papers, books and other information. And the results of the research conducted are then used to develop the right promotional strategy to increase investment.